Analysis of the Physical Condition of the Indonesian National Talented Atheletes Development Center - Rissa Dinar Amelia; Hadi; Feri Anggara (Journal of Physical Education Health and Sport, 2026)
To improve the quality of young athletes' development, the government, through the 2025 National Talented Athlete Development Center program, provides a regular training system complemented by routine monitoring and evaluation activities. Monitoring and evaluation are conducted to determine the success of the training program, observe athletes' progress, and serve as a reference for making decisions to improve the development program. Regular assessments help coaches and program managers identify progress or weaknesses in training activities. Physical condition testing using standardized tests is an important way to evaluate the success of a training program. Comparing assessment results between different stages provides a clear picture of an athlete's physical progress over time. By analyzing quantitative data descriptively, this progress can be presented as percentages and score categories, facilitating a clear understanding of program achievements. This study aims to analyze the physical development of athletes in the 2025 National Talented Athlete Development Center program based on the results of Monitoring and Evaluation (Monev) Phase 1 and Phase 2. The study uses a qualitative library research approach. The research sample consisted of 342 athletes who took physical tests in both evaluation phases. The data were analyzed using descriptive statistics in the form of percentages and distribution of score categories. The results show an increase in the average physical condition from 77% (adequate category) in Phase 1 to 80% (good category) in Phase 2. The proportion of athletes with scores <70% decreased from 23% to 12%. These findings indicate an increase in the effectiveness of physical training over a four-month period.